LEGISLAÇÃO URBANA: OCUPAÇÃO DO SOLO DE GRANDES EDIFÍCIOS NO MUNICÍPIO DE IPATINGA - Abreu, Renan Patrick Vaz de; Lisbanho, Rafael Teixeira; Oliveira, Vivian Moreno de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article identifies the causes and analyzes the consequences about crescent occupation of the buildings in the urban area of Cidade Nobre neighborhood in Ipatinga city, MG. Identifying flexibilizations of the laws of urban ground occupation. The identification was made comparing the urban parameter sof Law 3,408/2014 with parameter so flaws predecessor to it, such as the Term of Adjustment of Conduct signed between the Public Ministry and the City Hall in 2010 with the aim of controlling the soil occupation previously uncontrolled. The research is mainly aimed at addressing the impacts of traffic generation, population densification and real estate valuation, considering the data collected with the parnership of Ipatinga Municipal Government, duly compiled.